ANALISIS ENAM KOMPETENSI PENGAWAS MADRASAH - Aguslani Aguslani (Balai Diklat Keagamaan Bandung, 2019)
The Supervisor position in national education system is very strategic. Their duty to be an academic supervisor and evaluator to headmasters and teacher of madrasah s a subject to professional work. However, some researches have shown that supervisor professionalism level in Indonesia is still relatively low. The research tried to observe comprehensively on their academic, managerial, knowledge on research and development, personality, and social competencies. Research was done to collect data from supervisors in jabar with quantitative method, then analyzed descriptively and quantitatively. The research aims to find the level of supervisor competency in jabar that hopefully can be beneficial for policies to improve their level of professionalism. Research showed that their level of competencies is average. Government needs to intensify activities to enhance their knowledge and skill in supervising, mentoring and coaching headmaster, teachers, researching, and building partnership. Keywords: Analysis, Supervisor, Competences